Teaching Materials for Moral Beliefs in Madrasah - Lubis, Putriani; Sumiani Hasibuan; Febi Ananda; Musriana Luthfiah Hasibuan; Khoirun Nisah Lubis; Muhammad Irfan Saputra (Sekolah Tinggi Agama Islam Darul Qur'an Payakumbuh, 2024)
Moral creeds are one of the Islamic religious education materials. In the moral creeds material there is explained the basics of belief in Allah, as well as other monotheistic values. Then, the morals material is studied and explained about the concept of morals and the values ​​contained therein. Discussion of faith and morals is important so that students have complete knowledge and understanding of faith, and at the same time they are also able to realize the values ​​of their faith in real life in society in the form of good morals, based on what the Prophet Muhammad SAW taught. as a role model. For this reason, the field of faith study must be constructed from correct materials and included within the scope of the field of faith study. This research uses the literature method by first collecting study materials and materials from various sources, namely books, journals, articles and other sources related to teaching materials on moral beliefs in madrasah